Deep inguinal orifice: Anatomy, physiology, pathology, treatment - Croci, Fabio; Cordal, Adriana; Capurro, Ana (Cirugía del Uruguay, 1984)
Deep inguinal orificas and defensiva fascial structu• res are essential elements no only al the genesis but olmously also in the surgical treatment of externa! inguinal hernia. The valvular mechanism deter• mlned by the fascia transversalis at the interna! sup• port level, is a functional and biomechanic structure of great preciseness and complexity. 1st failure, either congenit or acquired is the factor causing the piercing of the oriflce and settlement into the peritoneal diverti• culum. Attemps at permanent cure must repair and res• tore this structure.